2014
DOI: 10.1002/ps.3900
|View full text |Cite
|
Sign up to set email alerts
|

Fitness costs of reproductive capacity and ovarian development in a Bt‐resistant strain of the cotton bollworm Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae)

Abstract: BACKGROUND The cotton bollworm Helicoverpa armigera has developed resistance to the insecticidal Cry1Ac toxins produced by Bacillus thuringiensis (Bt) in China. To gain a better understanding of the fitness cost associated with resistance evolution, reproductive capacities and ovarian development were examined in four strains of H. armigera: a Cry1Ac‐susceptible strain (96S); a Cry1Ac‐resistant strain fed on an artificial diet with Cry1Ac toxin for 135 generations (BtR); two strains derived from BtR: a strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…To analyse the function of HaKr‐h1 in JH‐mediated vitellogenesis and oocyte maturation, Kr‐h1 RNAi experiments were performed in female adults, and then the ovarian development status and number of eggs laid were recorded. Based on the characterization of ovarian development stages described previously (Zhang et al ., ), the ovarian developmental grade was measured at 2 and 4 days after dsRNA injection. The results showed that knockdown of HaKr‐h1 significantly delayed oocyte maturation, resulting in the retardation of ovary development.…”
Section: Resultsmentioning
confidence: 99%
“…To analyse the function of HaKr‐h1 in JH‐mediated vitellogenesis and oocyte maturation, Kr‐h1 RNAi experiments were performed in female adults, and then the ovarian development status and number of eggs laid were recorded. Based on the characterization of ovarian development stages described previously (Zhang et al ., ), the ovarian developmental grade was measured at 2 and 4 days after dsRNA injection. The results showed that knockdown of HaKr‐h1 significantly delayed oocyte maturation, resulting in the retardation of ovary development.…”
Section: Resultsmentioning
confidence: 99%
“…are the most damaging and cosmopolitan pest species. These species have well-adapted different agro-ecological zones around the globe from Asia to Africa to Europe (Zhang et al 2015). They are polyphagous pests with a wide range of host plants including: cotton, maize, gram, sesame, okra, tomato, potato, and many other fruit and vegetable crops (Aggarwal et al 2006;Nagoshi et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This trade-off strategy is not so exceptional in insects facing various stressful situations. For example, the resistance of females of the corn earworm Helicoverpa armigera against Bacillus thuringiensis toxin Cry1Ac was accompanied by the inhibition of reproduction caused by a decrease in Vg gene expression (Zhang et al, 2014(Zhang et al, , 2015. Similarly, in females of the rice stem borer Chilo suppessalis, application of sublethal doses of the insecticide chlorantraniliprole reduced Vg mRNA expression (Huang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%